Influence of Circular Supply Chain Practices on the Performance of Manufacturing Firms in Nairobi County, Kenya - Kinoti, Wilfred; Barasa, Peter (International Journal of Supply Chain Management, 2022)
Purpose: Previous studies conducted in Kenya and elsewhere in the world have investigated how circular economies affect various aspects of the firm's performance such as supply chain performance, distribution, customer service among others. The goal of this study was to investigate the influence of Circular Supply Chain Practices (CSCP) on the performance of the Manufacturing Firms in Nairobi County, Kenya. Methodology: The study adopted a descriptive Research design. The target population of this research was the eight hundred employees working in the160 manufacturing firms in Nairobi County, Kenya. It employed a stratified sampling method whereby a sample of 100 respondents were selected, and used questionnaires to collect data. It adopted descriptive and inferential statistics to evaluate the variables numerically whereby Statistical Package for Social Students (SPSS) was used in the data analysis. In determining the relationship between Circular Supply Chain Practices and the performance of manufacturing firms in Nairobi County, Kenya, the regression model was used. The data and results of the study were presented in tables. Findings: Findings showed that circular supply chain practices have positive and significant influence on performance of manufacturing firms in Nairobi County. The regression analysis reveals that 89.2% Variations in the performance of manufacturing firms in Nairobi County are as a result of circular supply chain practices with (R2=0.892) Unique Contribution to Theory, Practice and Policy: The study recommends that manufacturing firms should put in place mechanism to improve reverse logistics, green policy regulation, sustainable supply chain collaboration and product design practices. Further, the government should formulate adequate policies that would provide a good framework to make use of circular supply chain practices.